Comparison of the microbiological quality of water coolers and that of municipal water systems. - Lévesque, B (1994)
The microbiological quality of tap water and that of water from 50 water coolers located in residences and workplaces were comparatively studied. In addition, difference factors that might influence the bacteriological contamination of water dispensers were examined. Aeorbic and facultative anaerobic heterotrophic bacteria, total coliforms, and two indicators for fecal contamination (fecal coliforms and fecal streptococci) as well as three types of pathogenic bacteria (Staphylococcus aureus, Pseudomonas aeruginosa, and Aeromonas spp.) were enumerated. It was found that 36 and 28% of the water dispenser samples from the residences and the workplaces, respectively, were contaminated by a least one coliform or indicator bacterium and/or at least one pathogenic bacterium. The respective proportions of tap water samples contaminated in a similar fashion were 18 and 22%, much less than those observed for water coolers (Chi2(1) = 3.71, P = 0.05). We were unable to discern the dominant factors responsible for the contamination of water coolers, but cleaning the water dispenser every 2 months seemed to limit the extent of contamination.